Carbon Stock Estimation in the Mangrove Area of the Marine Station of Universitas Riau, Dumai - Intan Yunika Putri; Aras Mulyadi; Efriyeldi Efriyeldi; Ilham Ilahi; Benny Heltonika (Jurnal Perikanan dan Kelautan, 2026)
Mangrove forests can store more carbon than most terrestrial forest ecosystems, making them important for climate change mitigation. Their carbon sequestration potential depends on the trees' ability to absorb atmospheric CO₂ through photosynthesis. This study aimed to estimate biomass, carbon stock, and CO₂ sequestration in the mangrove area of the Marine Station of Universitas Riau, Dumai, Indonesia. The research was conducted from September to November 2025 at three stations representing terrestrial, riverine, and marine zones. Data were collected through DBH measurements of mangrove vegetation and sediment coring, supported by environmental parameters such as temperature, pH, and salinity. Mangrove density ranged from 1,200 to 2,388.33 individuals ha⁻¹, with the highest value at Station 2 and the lowest at Station 3. This pattern was positively related to biomass, vegetation carbon stock, and CO₂ sequestration. Estimated biomass reached 897.73 tons ha⁻¹, while vegetation carbon stock was 421.93 tons ha⁻¹. Sediment was the largest carbon pool, ranging from 1,896.10 to 2,202.97 tons ha⁻¹, with the highest value at Station 1. Total carbon stock reached 2,462.12 tons ha⁻¹. Statistical analysis showed a strong positive correlation among stand density, biomass, carbon stock, and CO₂ sequestration. Regression analysis indicated a significant relationship (R² = 0.502), meaning 50.2% of the variability in these parameters was explained by stand density. At the same time, the remainder was influenced by other factors such as stand age, substrate fertility, and planting distance.